The development of a psychosocial educational programme to facilitate the reintegration of incarcerated women who had dumped babies and / or committed infanticide - Sumpi, Ndempavali; Amukugo, Hans Justus (International Journal of Health, 2016)
This paper focused process followed on the development of a psychosocial educational programme to facilitate the reintegration process of women who had dumped their babies and / or committed infanticide.The development of the educational programme established was based on the survey guide suggested by Dickoff et al. (1968) namely agent, recipient, dynamic and terminus. According to the data analysis, the women who had dumped babies and / or committed infanticides were experiencing psychological and socioeconomic challenges, as well as reintegration, legal, and ethical challenges. The researcher decided to develop a psychosocial educational programme to address those challenges. The educational programme was also designed to meet the needs of women who had dumped babies and / or committed infanticide and to equip them with competencies; such as skills, knowledge, attitudes, and values to manage the psycho-social aspects and to facilitate their reintegration.The educational programme comprises, the aim of educational, objectives, contents of an educational programme educational approaches, programme development process, evaluation of an educational programme.